Repetitive out of hospital cardiac arrests following pregnancy: a case report of an unfortunate presentation of mitral annular disjunction - Van Berendoncks, An (Eur Heart J Case Rep, 2020)
BACKGROUND: Mitral annular disjunction (MAD) is an under-recognized cause of arrhythmic sudden cardiac death, especially in young women. The relation between MAD and the occurrence of arrhythmia during pregnancy has not yet been explored. We would like to stress the importance of careful echocardiographic examination and the vulnerable peripartum period. CASE SUMMARY: A 29-year-old woman survived an out of hospital cardiac arrest 4 months after delivery of her first child. The diagnosis was not clear and an implantable cardioverter-defibrillator (ICD) as secondary prevention was implanted. Her second pregnancy and delivery were uneventful. The 12-lead electrocardiogram demonstrated sinus rhythm with right bundle branch block, ventricular extra systoles (premature ventricular contractions), and a right superior axis, i.e. origin in the inferolateral basal left ventricle. Transthoracic 2D echocardiography showed myxomatous mitral valve disease with moderate mitral valve insufficiency with normal left and right heart dimensions and function. However, 4 weeks after delivery she experienced a sudden syncope at home. Implantable cardioverter-defibrillator reading revealed primary ventricular fibrillation, induced by a ventricular premature beat (VPB), terminated with a successful ICD shock. A frame-by-frame echocardiographic analysis of the mitral valve using biplane echocardiographic analysis allowed diagnosis of MAD with detachment of the root of the annulus from the posterolateral ventricular myocardium during systole. CONCLUSION: Mitral annular disjunction is an under-recognized cause of arrhythmic sudden cardiac death. Biplane echocardiographic analysis of the mitral annulus can identify MAD and as such may help for risk stratification and sudden cardiac death prevention. Careful follow-up is necessary especially during pregnancy and the postpartum period.